The kingship of Jesus in the Gospel of John - Kim, Sehyun; University of Sheffield Department of Biblical Studies
The purpose of this thesis is to study the kingship mitif with reference to the Johannine Jesus: his identity and function. To do so, I use postcolonialism as a major methodology. It leads us to an avenue from which to read the Gospel of John in the more complex and wider context, namely in the hybridised Jewish and Graeco-Roman worlds of the Roman Empire in the first century C.E. As a result, we gain a new perspective on the kingship of the Johannine Jesus, whose kingly identity is characterised by the hybridised Christological titles: Messiah, Son of God, Son of Man, Prophet, Saviour of the World, and Lord (My Lord and My God). It is stressed that these Christological terms are used in a unique and distinctive way in the Gospel of John to reveal the kingship of Jesus, particularly the title King (of the Jews) more explicitly.
For Johannine readers in the first century, who were exploited, suppressed, yet at odds with both the centre/the coloniser, and the margins/the colonised in the Roman Empire, the Gospel of John was deemed to reveal the identity of Jesus. Using many Christological titles, it presented Jesus as the universal king going beyond the Jewish Messiah(s) and the Roman emperors and also as the decoloniser who came to "his own" world to liberate his people from the darkness.
The main concern of the Gospel of John manifests itself in suggesting that Jesus is the One to solve every conflict in societies. In this respect, the ideology of the Johannine Jesus is very different from that of the earthly empire. It emphasises that love, freedom, service of the centre for the margins, and forgiveness are the ruling forces in the new world wwhere the Johannine Jesus reigns as king. Raising an awareness of these ideologies, the Gospel of John asks the readers to overcome the conflicting world shrouded in darkness, thenceforth entering the new world shining in light.
A thesis submitted to the Faculty of the Department of Biblical Studies [University of Sheffield] in fulfillment of the requirements for the degree Doctor of Philosophy, May 2010.
Includes bibliographiucal references.
Keywords: Jesus Christ -- kingship; Bibe. -- criticism, interpretation, etc